El Modelo Interactivo, una innovación curricular en matemática: resultados de su implementación en el contexto educacional chileno - Villarreal Farah, Gonzalo (2011)
This paper analyzes the results of the implementation of a model curriculum innovation in mathematics in public schools in Chile. The resultscome from the project Enlaces Matemática. This information is supplemented with data from the study leading to Ph. D. degree by oneof the authors. This project is based on interactive mathematical teaching model developed by Comenius Center, University of Santiago (Oteiza &Miranda, 2004), whose model has been designed, developed and tested from the classrooms. From the evidence examined to ensure it is concludedthat changes in teaching practices and improvements in learning achievement, it requires a curricular model that integrates naturally differentresources for teacher and student, consider the total content of current curriculum. In addition, it requires a process of fostering and ongoing support, focusing on the appropriation of the model by the participantsand to support changes in the roles involved. It is shown consistently that students participating in the project perform better than students not involved in this. This allows inference suggestions and recommendations on curricular innovation processes, changing teaching practices, changes in roles of the actors of the educational process and strategies to support teachers and students in the appropriation of these innovations.